Analisis Kebijakan Sekolah Siaga Kesehatan Mental: Dampaknya terhadap Peran Guru BK dalam Membantu Strategi Coping Siswa Overthinking - Bagus Ahmad Nur Mukhlison; Nadia Tussyafa'ah; Nabila Azzahra; Ridha Nurul Fadhilah Azzahro; Vany Dwi Putri (CV. AKIRA JAVA BULU, 2026)
Anxiety and overthinking among adolescents are becoming increasingly common, particularly due to pressure from family, friends, and uncertainty about the future. The purpose of this community service project is to identify instances of overthinking among students at SMP Negeri 4 Cirebon and to determine how Guidance and Counseling (BK) teachers address this issue. To achieve this objective, a qualitative descriptive approach was employed, involving interviews and direct observations of BK teachers and a number of students. The results of the study indicate that students who overthink often fall asleep in class, appear lethargic, isolate themselves, and have difficulty concentrating. Some students even experience such severe anxiety that they must be referred to a psychologist.